Variation in Antibiotic Prescribing among Emergency Departments, Urgent Care Centers, and Retail Health Clinics in the United States, 2014. (4th October 2017) - Palms, Danielle; Hicks, Lauri; Hersh, Adam L; Bartoces, Monina; Hyun, David; Zetts, Rachel; Fleming-Dutra, Katherine
Abstract: Background: At least 30% of antibiotic courses prescribed in physician offices' and emergency departments (EDs) are unnecessary, but little is known about other ambulatory settings. The study aimed to assess antibiotic prescribing for acute respiratory conditions across U.S. EDs, urgent care centers (UCs), and retail health clinics (RHs). Methods: We included visits to EDs, UCs and RHs based on claims from individuals < 65 years old with medical and pharmacy benefits captured in the 2014 Truven MarketScan Commercial Claims and Encounters Database, a convenience sample of employer-based health insurance. Claims for dispensed systemic antibiotics were linked to the most recent ED, UC and RH visit within 3 days for oral antibiotics and on the same day for parenteral antibiotics. Diagnoses were assigned to each visit based on a previously-described tiered system to assign the most likely indication for antibiotics. Antibiotic-inappropriate respiratory conditions (i.e., viral respiratory infections, asthma, and allergy) were identified, and the percent of visits leading to antibiotics were calculated with 95% confidence intervals (CI) by setting. Results: In 2014, antibiotics were prescribed in 13.8% (95% CI 13.7–13.8) of 4, 954, 084 included ED visits, 38.8% (38.8–38.9) of 2, 831, 950 UC visits, and 36.3% (35.9–36.6) of 59, 599 RH visits. Antibiotic-inappropriate respiratory conditions accounted for 5.4% of ED visits, 16.4% of UC visits, and 17.2% of RH visits. UCs had the highest percent of antibiotic prescriptions for all antibiotic-inappropriate respiratory conditions (45.3%, 95% CI 45.2–45.5), followed by EDs (24.5%, 24.3–24.6) and then RHs (14.4%, 13.8–15.1). This pattern persisted when examined by diagnosis (figure). Conclusion: Antibiotic prescribing for antibiotic-inappropriate respiratory infections was common in these settings. UCs are a particularly important target for antibiotic stewardship. Disclosures: All authors: No reported disclosures.